Cultivating elok budi character value in elementary school - Elpri Darta Putra; Bunyamin Maftuh; Mamat Supriatna (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Character education in primary schools is essential to shaping children's moral values and good behavior. This research uses the literature study method to understand how the character values of Eloklah Budi can be effectively applied in the daily lives of elementary school students. Data were obtained from various sources, such as books, journal articles, and educational policies, which were analyzed to describe practical approaches to integrating character values. The results show that character education focusing on the concept of "Eloklah Budi" in primary schools emphasizes the development of cognitive and academic aspects and the formation of dignified and highly ethical character in students. Approaches through the formal curriculum and extracurricular activities have proven effective in teaching students honesty, responsibility, politeness, and empathy. The holistic approach to character education also recognizes local cultural and religious values as key elements in building a strong and diverse character.